2020
DOI: 10.1364/ol.395922
|View full text |Cite
|
Sign up to set email alerts
|

Distributed and dynamic strain sensing with high spatial resolution and large measurable strain range

Abstract: A distributed and dynamic strain sensing system based on frequency-scanning phase-sensitive optical time domain reflectometry is proposed and demonstrated. By utilizing an RF pulse scheme with a fast arbitrary waveform generator, a train of optical pulses covering a large range of different optical frequencies, short pulse width, and high extinction ratio is generated. Also, a Rayleigh-enhanced fiber is used to eliminate the need for averaging, allowing single-shot operation. Using direct detection and harness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Finally, there is yet another kind of methods that are based on using the dependence on wavelength of the interference from the signals coming from a particular location in the fiber. These can work by directly changing the wavelength of the interrogating pulses launched into the fiber [2] [3] or by using chirped pulses in which the wavelength dependence of the interference is translated to a time dependence [4]. In either case, the excitation affecting the fiber can be quantified by the shift that it induces in the interference pattern.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, there is yet another kind of methods that are based on using the dependence on wavelength of the interference from the signals coming from a particular location in the fiber. These can work by directly changing the wavelength of the interrogating pulses launched into the fiber [2] [3] or by using chirped pulses in which the wavelength dependence of the interference is translated to a time dependence [4]. In either case, the excitation affecting the fiber can be quantified by the shift that it induces in the interference pattern.…”
Section: Introductionmentioning
confidence: 99%
“…The enhancement in the intensity of the backscattered signal has been achieved by either forming a continuous grating along the fibre 32 or inscribing individual reflectors at fixed intervals in the core of the fibre 33 . In 2020, Zhang et al 34 have shown that the spatial resolution of a conventional DAS system that operates based on φ -OTDR interrogation technique can be reduced to as low as 20 cm if a continuous grating enhanced backscattering (CGEB) fibre is used as a sensing medium. In the following year, Xiong et al 35 have used CGEB fibre to demonstrate a DAS system with 28 cm resolution, but over a much longer sensing range of up to 920 m. Despite these successful demonstrations, since the intensity of the backscattered light in a CGEB fibre is proportional to the duration of the probe pulse, DAS systems based on this fibre still encounter the same trade-off between the spatial resolution and SNR.…”
Section: Introductionmentioning
confidence: 99%
“…This limitation restricts the use of φ-DAS in applications that require measurement of high strain-rates over long distances such as analysis of large-magnitude earthquakes or evaluation of railway track behavior [3,17]. Although, a number of φ-DAS systems capable of measuring relatively large strain levels have recently been demonstrated, the sensing range in none of those studies were exceeding [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%